2017
DOI: 10.1016/j.exer.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

BetaB2-crystallin mutations associated with cataract and glaucoma leads to mitochondrial alterations in lens epithelial cells and retinal neurons

Abstract: Crystallin proteins are the most prominent protein of the lens and have been increasingly shown to play critical roles in other tissues, especially the retina. Members of all 3 sub-families of crystallins, alpha-, beta- and gamma-crystallins have been reported in the retina during diabetes, traumatic injury and other retinal diseases. While their specific role in the retina is still unclear and may vary, beta-crystallin proteins have been shown to play a critical role in ganglion cell survival following trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Consistent with the solubility data presented in Figure 1 , the single and double βB2-crystallin mutants displayed a diffuse pattern indistinguishable from the one observed with the WT protein. The same staining patterns were observed for the βB2-crystallin WT and the triple βB2-crystallin mutant also in lens cells [ 2 ].…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Consistent with the solubility data presented in Figure 1 , the single and double βB2-crystallin mutants displayed a diffuse pattern indistinguishable from the one observed with the WT protein. The same staining patterns were observed for the βB2-crystallin WT and the triple βB2-crystallin mutant also in lens cells [ 2 ].…”
Section: Resultssupporting
confidence: 66%
“…Only the full gene conversion lead to a loss of solubility, shown by the triple mutant being found almost exclusively in the insoluble fraction ( Figure 1 ). Interestingly, this effect is partially cell-type specific as we previously reported that when we expressed the triple mutant βB2-crystallin in lens epithelial cells, we observed a less dramatic shift in solubility of the triple mutant, with 35% of the protein remaining soluble [ 2 ].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Crystallins are the predominant lens structural proteins of mammals and have a significant function in providing transparency and light transmission to the eye lens 32 . However, mutations in the genes encoding crystallin proteins lead to abnormal expression, which might disrupt lens opacity and even cause blindness 12 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 99%